What does sociocultural learning and literacy look like in an adult employment preparation program? - Pinsent-Johnson, Christine (University of Ottawa (Canada), 2005)
The closely aligned theoretical discussions of situated learning (Lave & Wenger, 1991; Wenger, 1998) and situated literacy (Barton & Hamilton, 1998; Hamilton, 2000) were used to explore literacy and learning activities in an adult literacy program that combined literacy education and employment preparation in three distinct learning settings. The parallel discussions provided a socioculturally-based framework that permitted a detailed analysis of what learning and literacy looked like. Guiding the study was the following question: How do situated views of literacy and learning contribute to an understanding of the employment preparation program and its three settings? Using the frameworks of situated learning and literacy to closely examine the employment preparation program revealed disconnects between the work settings (the coffee shop and job placements) and the class setting, and subsequently between the notions of learning literacy and learning about work. Among the study's contributions is a clearer conceptualization of a broad definition of literacy, in which the development of literacy practices becomes the focus for supporting the development of adult literacy education. Policy contributions examine the role of the provincial program funder and how it has a structure to support the development of a practice-based approach in adult literacy education. Finally, contributions to research propose the use of an analytical tool to further understand sociocultural learning, and specifically literacy and learning practices, in adult literacy programs. (Abstract shortened by UMI.)
Keywords: Education, Adult and Continuing.; Education, Reading.